Enhancing Autophagy Protects Against Sepsis-Induced Neuromuscular Dysfunction Associated with Qualitative Changes to Acetylcholine Receptors. Issue 1 (July 2019) - Chen, Jingyuan; Min, Su; Xie, Fei; Yang, Jun; Wang, Xin
Abstract : ABSTRACT: Sepsis-induced myopathy is a heavy burden for patients during respiratory failure as well as after discharge, which could be characterized with qualitative changes to nAChR in a rat model of sepsis, regulated by NRG-1. Autophagy is an innate immune defense mechanism against microbial challenges. We found neuromuscular dysfunction in anterior tibial muscle of male Sprague-Dawley rats 24 h after cecal ligation and puncture (CLP). CLP resulted in increased systemic and local inflammation in anterior tibial muscle tissue. The start-up phase of autophagy, as measured by LC3II, was activated immediately after CLP and continued until 24 h; the degradation phase was suppressed until 24 h, after a brief increase at 4 h (revealed by p62). NRG-1 first increased, and then decreased to a level lower than that in the sham group. Meanwhile, expression of γ- and α7- acetylcholine receptors was detected at 8 and 16 h after CLP; levels increased continuously until 24 h. Subsequently, we investigated the significance of autophagy in CLP-induced neuromuscular dysfunction by treatment with rapamycin or 3-methyladenine, which were classical pharmaceuticals for enhancing or suppressing autophagy. Rapamycin activated autophagy, limited the CLP-induced systemic pro-inflammatory response and blood bacterial load without affecting local inflammatory response, upregulated NRG-1, downregulated γ- and α7-acetylcholine receptors, and improved 7-day neuromuscular function and survival rate. In contrast, 3-methyladenine enhanced local inflammatory response, suppressed autophagy, worsened 7-day neuromuscular function. We conclude that impaired autophagy may contribute to sepsis-induced neuromuscular dysfunction in young male rats. Enhancing autophagy with rapamycin alleviated qualitative changes to acetylcholine receptors without triggering local anti-inflammatory response and improved anterior tibial muscle function in septic early phase (24 h) as well as in septic chronic phase (7d). Enhancing autophagy soon after sepsis is a potential strategy for treatment of sepsis-induced myopathy.